Study the Effect of the Seed Grape vitis vinifera Plant Extract on Some Pathogenic Bacteria and Fungi - Sumayah Sami Hashim (Journal of Global Pharma Technology, 2020)
Aqueous extract of grape seed was prepared for the purpose of studying its effect in inhibiting the growth of some pathogenic bacterial and fungal isolates. Candida albicans, Escherichia coli, Staphylococcus aurus, Klebsiella pneumoniae, and Proteus mirobillis. The effect of extract concentrations was studied and the effect varied with the concentration on these isolates. The effect of the same extract on C.albicans was studied. The result was also show the higher concentration of the extract appeared the greater inhibitory effect on C. albicans. The effect of some antibacterial and antifungal agents was also studied. The inhibitory effect varied according to the species of bacteria.at the other hand nystatin showed higher inhibitory effect with inhibition zone 8, 9, 10mm. Keywords: Fungi, Pathogenic Bacteria, Seed Grape vitis vinifera, Plant Extract.